2014
DOI: 10.1007/s11010-014-2308-8
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT-enhancer binding protein (C/EBP) β regulates insulin-like growth factor (IGF) 1 expression in porcine liver during prenatal and postnatal development

Abstract: IGF1 expression regulation attracts numerous interests because of its important role during mammalian growth and development. Domestic pig can be used as a valuable animal model to investigate human development since they share the high similarity in general physiology and metabolism. In this study, we examined the expression pattern of IGF1 and found it associated with liver C/EBP β expression pattern in porcine liver during embryonic and postnatal development. Both IGF1 and C/EBP β expression in liver mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…The effect of C/EBPs on cell apoptosis and differentiation is mediated by their ability to bind upstream CCAAT elements to regulate gene expression (43). However, studies have shown that these factors also regulate cell fate through protein-protein interactions independent of their transcriptional activity (45,85,86). Our results confirm that C/EBPb regulates IGFBP5 by binding to its promoter region directly.…”
Section: Discussionsupporting
confidence: 77%
“…The effect of C/EBPs on cell apoptosis and differentiation is mediated by their ability to bind upstream CCAAT elements to regulate gene expression (43). However, studies have shown that these factors also regulate cell fate through protein-protein interactions independent of their transcriptional activity (45,85,86). Our results confirm that C/EBPb regulates IGFBP5 by binding to its promoter region directly.…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, our data supported crucial function of IGFBP1 in the current study. Increasing evidence suggested an important role of IGFBP in the development and progression of several types of cancers [ 16 18 , 47 ]. However, the expression and function of IGFBP1 in HCC development remains controversial, and little is known about its true role including diagnostic and prognostic values in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin-like growth factor (IGF) binding protein 1 (IGFBP1), a pivotal protein of the IGF system, has been shown to be implicated in many cellular functions including proliferation, development, apoptosis, DNA damage repair, and tumor growth through IGF-dependent and -independent mechanisms [ 16 18 ]. Early report showed that inhibition of IGF receptor 1 function by IGFBP1 inhibited breast cancer cell growth [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is necessary to identify the core region of the promotor first. In light of lacking eukaryotic promoter and enhancer sequences in pGL3-basic vector, the sequences inserted upstream from luc + affect the expression of the luciferase activity in cells ( Tang et al, 2015 ). Using this vector, we found that the 5′-flanking region from -195 to +25 bp of porcine Abcb1 gene significantly influenced the promoter activity ( Figure 3 ), suggesting that the core promoter is located in this region and the regulatory elements of this region may affect the promoter activity of porcine Abcb1.…”
Section: Discussionmentioning
confidence: 99%